International fragmentation and relative wages in the UK - Holger Görg; Alexander Hijzen; Robert C. Hine (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2001)
While growing wage inequality is of ongoing concern in many developed countries, there still does not exist a consensus on the predominant source of this trend. Some argue that skill-biased technological change is responsible for the shift in the relative demand of skilled workers while others hold increased import competition from low-wage countries reducing employment for the unskilled responsible for the growing income divide within countries. This paper re-examines the trade-based explanation by focussing on international outsourcing. In a recent paper, Feenstra and Hanson (1996) estimate the effect of international outsourcing on wage inequality in the US. This paper extends the FH approach using more detailed definitions of import penetration and outsourcing as well as data for UK manufacturing industries for the period 1982-1996. The econometric results suggest that technical change and import penetration matter for wage inequality (although the effect of the latter depends crucially on whether or not estimations are weighted) while the role of outsourcing cannot be clearly determined.
Keywords: 330; Lohnstruktur; Einkommensverteilung; Außenhandelsliberalisierung; Outsourcing; Verarbeitendes Gewerbe; Internationale Arbeitsteilung; Großbritannien